2004
DOI: 10.3758/cabn.4.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Brighter noise: Sensory enhancement of perceived loudness by concurrent visual stimulation

Abstract: Two experiments investigated the effect of concurrently presented light on the perceived loudness of a low-level burst of white noise. The results suggest two points. First, white noise presented with light tends to be rated as louder than noise presented alone. Second, the enhancement in loudness judgments is resistant to two experimental manipulations: varying the probability that light accompanies sound and shifting from a rating method to a forced choice comparison. Both manipulations were previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 17 publications
5
71
1
1
Order By: Relevance
“…In a bimodal setting, Chen and Yeh (2009) showed that the perception of visual events was enhanced by accompaniment with auditory stimulation, thus supporting the facilitation effect of sound on vision. Similarly, Odgaard et al (2004) showed that concurrent visual stimulation could enhance the loudness of auditory white noise, and Arabzadeh et al (2008) confirmed that a visual stimulation could improve the discrimination of somatosensory stimulation, thus providing support for the facilitation effect of vision on both auditory and somatosensory modalities. Some researchers have also analyzed multisensory facilitation using electrophysiological methods at both the cortical level and neuronal level (Jiang et al 2002;McDonald et al 2003;Molholm et al 2002;Rowland et al 2007).…”
Section: Introductionmentioning
confidence: 67%
“…In a bimodal setting, Chen and Yeh (2009) showed that the perception of visual events was enhanced by accompaniment with auditory stimulation, thus supporting the facilitation effect of sound on vision. Similarly, Odgaard et al (2004) showed that concurrent visual stimulation could enhance the loudness of auditory white noise, and Arabzadeh et al (2008) confirmed that a visual stimulation could improve the discrimination of somatosensory stimulation, thus providing support for the facilitation effect of vision on both auditory and somatosensory modalities. Some researchers have also analyzed multisensory facilitation using electrophysiological methods at both the cortical level and neuronal level (Jiang et al 2002;McDonald et al 2003;Molholm et al 2002;Rowland et al 2007).…”
Section: Introductionmentioning
confidence: 67%
“…Nonetheless, a number of studies have yielded results compatible with early sensory interactions between stimuli from two sensory modalities. For example, the presence of a light can make white noise sound louder (Odgaard et al, 2004) and improve detection of threshold stimuli (Lovelace et al, 2003) in a manner consistent with an early sensory interaction. However, the opposite effect (white noise making a light seem brighter) appears to be the result of a response bias or other post-sensory process (Odgaard et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Odgaard et al (2004) showed that white noise presented with light tends to be rated as louder than noise presented alone. Because listeners in the present experiment were positioned in front of a lighted 17 inch flat-panel monitor for all the measurements, the influence of brightness would have been about constant for all measurements.…”
Section: B Multisensory Interactionsmentioning
confidence: 99%